2019
DOI: 10.3389/fnagi.2019.00321
|View full text |Cite
|
Sign up to set email alerts
|

A Delayed Advantage: Multi-Session Training at Evening Hours Leads to Better Long-Term Retention of Motor Skill in the Elderly

Abstract: The acquisition and retention of motor skills is necessary for everyday functioning in the elderly and may be critical in the context of motor rehabilitation. Recent studies indicate that motor training closely followed by sleep may result in better engagement of procedural (“how to”) memory consolidation processes in the elderly. Nevertheless, elderly individuals are mostly morning oriented and a common practice is to time rehabilitation programs to morning hours. Here, we tested whether the time-of-day where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 79 publications
(123 reference statements)
4
6
0
Order By: Relevance
“…Moreover, significant qualitative changes occurred in the tapping pattern (vis à vis the pattern attained at the end of the session but also compared with the initial sequence tapping pattern) overnight in the Eve, but not in the Morn group; these qualitative changes were well maintained (and even enhanced) a week later. We conjecture that these differences in the offline reorganization of the movement routine may account for slower forgetting rates that were observed in the same Eve group participants at the 7-mo retest after the completion of the multisession training protocol ( Gal et al 2019 ). In order to gain insight into the nature of underlying processes and their effect on memories, changes in the tapping pattern should be considered together with changes in performance speed ( Gabitov et al 2017 ; Gabitov et al 2019a ).…”
Section: Tapping Patternsmentioning
confidence: 93%
See 3 more Smart Citations
“…Moreover, significant qualitative changes occurred in the tapping pattern (vis à vis the pattern attained at the end of the session but also compared with the initial sequence tapping pattern) overnight in the Eve, but not in the Morn group; these qualitative changes were well maintained (and even enhanced) a week later. We conjecture that these differences in the offline reorganization of the movement routine may account for slower forgetting rates that were observed in the same Eve group participants at the 7-mo retest after the completion of the multisession training protocol ( Gal et al 2019 ). In order to gain insight into the nature of underlying processes and their effect on memories, changes in the tapping pattern should be considered together with changes in performance speed ( Gabitov et al 2017 ; Gabitov et al 2019a ).…”
Section: Tapping Patternsmentioning
confidence: 93%
“…In a recent study, following a multisession training on a finger tapping sequence task, we found that elderly participants who trained in the evening hours had significantly lower forgetting rates over a 6-mo period, than participants receiving morning training ( Gal et al 2019 ). That implies that evening training in the elderly may better engage (and sustain) memory consolidation processes and thus result in a more robust skill representation.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Participants were trained to perform accurately and repeatedly a five-element sequence by tapping a 4-key response pad with their left (non-dominant) hand (Figure 3.a). This computerized version of the sequential finger tapping task, adapted from Karni, et al, (Karni, 1995;Karni et al, 1998), has been widely used to study mnemonic processes underlying learning of a new motor skill ( Albouy et al, 2015;Censor et al, 2010;Gabitov et al, 2019;Gal et al, 2019;King et al, 2017;Walker et al, 2002). For a recent review, see Doyon et al, (2018).…”
Section: Motor Sequence Learning Taskmentioning
confidence: 99%